MENGUKUR KONTRIBUSI LANGGANAN E-JOURNAL SCIENCEDIRECT TERHADAP PRODUKTIVITAS PERGURUAN TINGGI MENGGUNAKAN STUDI BIBLIOMETRIK: STUDI KASUS UNIVERSITAS ANDALAS - Saputra, Andi (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2018)
This study aims to measure the level of productivity of authors affiliated with Andalas University in journal published by ScienceDirect, to illustrate the level of contribution and utilization rate of e-journal subscriptions at Andalas University. Descriptive bibliometric method is used to measure the researcher's performance. Data is retrieved over the last 10 years. Data collection techniques from the ScienceDirect use advanced search facilities, typing the